In search of the generative question : a hermeneutic approach to pedagogy - Graaff, Johann (School of Education, 2014)
This dissertation investigates, first, the kinds of transformation that have occurred in the perceptions and identities of a first year sociology class at the University of Cape Town (UCT), and, second, the learning experiences that have led to, or been associated with, those changes. It does that through Hans-Georg Gadamer's hermeneutics. On the first issue, Gadamer proposes that the social sciences brings individuals to a meeting with the alien, and that this meeting effects a transformation of the self. This means both (following Jardine) to 'return life to its original difficulty', and (following Kerdeman) to be 'pulled up short'.